Cost and practical : based concept for innovative design of minimum offshore structures - Jitrada Buacharoen; Chiu, Gregory L.F.; Widjaja, Joko Harsono; Pornpong Asavadorndeja; RTG Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2010)
This thesis presents the innovative design of minimum offshore stru ctures for marginal field development in the Gulf of Thailand ( GOT). The practical offshore work and optimal cost are used as main consideration of this analysis. The models were proposed by reviewing the ex isting minimum offshore structure design concepts around the word. Braced monopod, Tri pod and Tetra-pod with suction piles are the case study. The design and analysis of to tal nine (9) models were carried out by performing Quasi-static in-place an alysis to verify the structural strength and serviceability of these platforms in designed water depth 15m, 25m and 35m. The 1-year and 50-year return period are taken as design criteria for platform operating and extreme storm conditions respectively. Two (2) concepts of tr ansportation and installation: jack up rig and self-installing concepts are de veloped and assessed the cost. The results show that these three (3) platform configurations can be install in the marginal field in the GOT by using these two (2) instal lation concepts. Self-installing is cheaper than jack up rig method. Braced-monopod is viab le to be an unmanned platform due to optimal structural strength and cheapest while Tripod is the most suitable for manned platforms.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Offshore Technology and Management, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 2010
Keywords: Offshore structues -- Thailand, Gulf of